Impact of Body Mass Index and Comorbidities on Outcomes in Upper Extremity Nerve Transfers - Head, Linden K.; Médor, Maria C.; Karir, Aneesh; Wolff, Gerald; Boyd, Kirsty U. (Journal of Reconstructive Microsurgery, 2021)
Background There is a paucity of research investigating the impact of patient comorbidities, such as obesity and smoking, on nerve transfer outcomes. The objective of this retrospective cohort study was to evaluate the impact of body mass index (BMI) and comorbidities on the clinical outcomes of upper extremity nerve transfers.Methods A retrospective cohort study was executed. Patients were eligible for inclusion if they had an upper extremity nerve transfer with a minimum of 12-months follow-up. Data was collected regarding demographics, comorbidities, injury etiology, nerve transfer, as well as preoperative and postoperative clinical assessments. The primary outcome measure was strength of the recipient nerve innervated musculature. Statistical analysis used the Mann-Whitney U test, Wilcoxon signed-rank test, and Spearman's rho.Results Thirty-eight patients undergoing 43 nerve transfers were eligible for inclusion. Patients had a mean age of 48.8 years and a mean BMI of 27.4 kg/m2 (range:19.7–39.0). Injuries involved the brachial plexus (32%) or its terminal branches (68%) with the most common etiologies including trauma (50%) and compression (26%). Anterior interosseous nerve to ulnar motor nerve (35%) was the most common transfer performed. With a mean follow-up of 20.1 months, increased BMI (p = 0.036) and smoking (p = 0.021) were associated with worse postoperative strength.Conclusion This retrospective cohort study demonstrated that increased BMI and smoking may be associated with worse outcomes in upper extremity nerve transfers—review of the literature yields ambiguity in both regards. To facilitate appropriate patient selection and guide expectations regarding prognosis, further experimental and clinical work is warranted.
Keywords: nerve transfer; peripheral nerve; body mass index